Optimising the antibiotic treatment of uncomplicated acute appendicitis: a protocol for a multicentre randomised clinical trial (APPAC II trial) - Haijanen J; Sippola S; Grönroos J; Rautio T; Nordström P; Rantanen T; Aarnio M; Ilves I; Hurme S; Marttila H; Virtanen J; Mattila A; et al. (My University, 2022)
Discussion
To our knowledge, APPAC II trial is the first randomised controlled trial comparing per oral antibiotic monotherapy with intravenous antibiotic therapy continued by per oral antibiotics in the treatment of uncomplicated acute appendicitis. The APPAC II trial aims to add clinical evidence on the debated role of antibiotics as the first-line treatment for a CT-confirmed uncomplicated acute appendicitis as well as to optimise the non-operative treatment for uncomplicated acute appendicitis.